Tingkah laku keibubapaan dan penyesuaian tingkah laku anak dalam keluarga berisiko di luar bandar - Arshat, Zarinah; Baharudin, Rozumah; Juhari, Rumaya; Kahar, Rojanah (Universiti Putra Malaysia Press, 2002)
This study aims to determine the relationships between family background factors (mother's educational level, family income and number of children) and quality of parental behavior with children behavioral adjustment (resiliency, self-esteem and academic achievement) in at-risk families. A total of 201 Malay mother-child dyads from rural areas in Kelantan, Kedah, Selangor and Johor who fulfill the selection criteria (poor and have at least one child aged 7-12 years) were selected as respondents for the study. Respondents were interviewed face-to-face using questionnaire. Parental behavior was measured using Supportive Parenting Scale (Simons et al. 1992). Child's resiliency is measured using Resiliency Attitudes Scales (Bischoe & Harris 1994) while Hare (1985) Self-Esteem Scale was utilized to measure child's self-esteem. The children's academic achievement is indicated by their score on five selected subjects, namely, Bahasa Melayu, Engish, Science, Mathematics and the Islamic Study. Results show that parental behavior and behavioral adjustment of the children are low. Mothers' education is significantly related to child self-esteem (r= 0.18, p ≤ .05) and academic achievement (r= 0.19, p ≤ .05). Families with higher level of risk and with greater number of children are found to have children with low levels of academic achievement and resiliency. Number of children have negative and significant relationship (r= - 0.16, p ≤ .05) with child's resiliency. Findings also reveal that level of risk correlate significantly with child's academic achievement (r= - 0.26, p ≤ .05). In addition the quality of parental behavior is positively related to the level of child's self-esteem (r= 0.17, p ≤ .05). Multiple regression analyses indicate that mother's education (? =0.16, p ≤ .05) and quality of parental behavior (? = 0.15, p ≤ .05) are unique predictors of child's self-esteem ( F = 5.55, p ≤ .05). The findings also reveal that mother's education (? = 0.18, p ≤ .05) determines child's academic achievement (F = 2.87, p ≤ .05). The study imply that mother's education and quality of parental behavior influence behavioral adjustment of children in rural at-risk families.